2018
DOI: 10.1007/s00221-018-5362-8
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment during a climbing traverse: implications for search and rescue climbing

Abstract: Cognitive resource limitations can impair one's ability to multitask. Previous research has shown that climbing is a particularly demanding task, and does not neatly fit into existing cognitive resource models. Climbing is a task relevant to firefighting and search and rescue, and operators often must also handle communication and navigation tasks in tandem. We present the results of a study where a naturalistic narrative memory task was paired with a climbing traverse. As hypothesized, both climbing and memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The influence of exercise on human physiology also depends on the mode of exercise, muscle involvement, and possibly changed body position (Labourne & Tomporowski, 2010). The combined effects of PE and the additional physiological (e.g., ambient pressure, submersion, body position, temperatures) or psychological (e.g., stress or fear of falling) demands of extreme environments on cognitive performance have already been investigated (Epling, Blakely, Edgar, Russell, & Helton, 2018; Stets & Helton, 2018; Yan, 2014). As such, fast processing speeds, decision-making abilities, and flexible behaviors are of high relevance to human safety and success if PE is paired with work conducted in extreme environments that require efficient adaption (e.g., while underwater or during prolonged episodes of microgravity; Martin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of exercise on human physiology also depends on the mode of exercise, muscle involvement, and possibly changed body position (Labourne & Tomporowski, 2010). The combined effects of PE and the additional physiological (e.g., ambient pressure, submersion, body position, temperatures) or psychological (e.g., stress or fear of falling) demands of extreme environments on cognitive performance have already been investigated (Epling, Blakely, Edgar, Russell, & Helton, 2018; Stets & Helton, 2018; Yan, 2014). As such, fast processing speeds, decision-making abilities, and flexible behaviors are of high relevance to human safety and success if PE is paired with work conducted in extreme environments that require efficient adaption (e.g., while underwater or during prolonged episodes of microgravity; Martin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are controversial debates about these effects, the general consensus is that acute/moderate PE tends to have a positive effect on cognition in regard to measurements taken during or directly after PE (Chang & Etnier, 2009; Chang et al, 2012). Given the relevance of cognitive performance for mission success and safety in extreme environments or situations (Epling et al, 2018; Stets & Helton, 2018; Yan, 2014), further contextual investigation is needed to determine the influence of PE on cognitive functions (Martin et al, 2019). This is especially relevant in critical and non-routinized situations that require quick decision making and when individuals are exposed to high physical workloads.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have begun to use more naturalistic physical tasks (Blakely, Kemp, & Helton, 2016; Darling & Helton, 2014; Epling, Blakely, Edgar, Russell, & Helton, 2018; Epling, Blakely, Russell, & Helton, 2016; Green, Draper, & Helton, 2014; Green & Helton, 2011; Helton, Green, & de Joux, 2013). Regarding the dual-task interference between cognitively demanding tasks and physically demanding tasks, these studies have found substantial interference between word-free recall and both running over natural terrain and climbing performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the verbal memory task used in both studies above required participants listen to and later freely recall a list of discrete, unrelated words, which has minimal ecological validity. In response to a similar problem in their own research, Epling and colleagues developed a narrative memory task, said to be more applicable to real world demands (Epling, Blakely, Edgar, Russell, & Helton 2018;2019). Unlike a free recall task, understanding verbal cues from an individual's surroundings or remembering the gist of a conversation could be very important in real-world situations (Epling, Blakely, et al, 2018): poor comprehension or failed memory of a situation or conversation can lead to accidents or mistakes (Edgar & Edgar 2007).…”
mentioning
confidence: 99%
“…All rights reserved. 10.1177/1071181320641056 conversation could be very important in real-world situations (Epling, Blakely, et al, 2018): poor comprehension or failed memory of a situation or conversation can lead to accidents or mistakes (Edgar & Edgar 2007).…”
mentioning
confidence: 99%